Lado Kralj med gledališko teorijo in prakso - Toporišič, Tomaž (Primerjalna književnost, 2018)
This article analyzes Lado Kralj's theatrical and scientific-research work. As clearly seen from a historical and critical overview of his work from the end of the 1960s to the present, Lado Kralj is a key figure in both fields and a personality uniquely interweaving the fields of theory and practice. He started his career as a literary theoretician who built himself with the thought from the theories of comparative literature of Anton Ocvirk and the analysis of the poetics of the fiction and drama opus of Slavko Grum. Following his collaboration with theater director and performance theorist Richard Schechner in New York he co-founded in Ljubljana two of the most important experimental Slovene theaters (EG Glej and Pekarna) in the 1970-s. His artistic work within the field of experimental theatre influenced his exploration of historical avant-garde, especially expressionism from 1970-s till present. Following his artistic leadership of the Ljubljana National Theatre his work focused on the role of a professor at the Ljubljana Faculty of Arts encouraging his important research into the theory of drama and theatre.
Keywords: EG Glej; eksperimentalno gledališče; ekspresionizem; književnost in gledališče; Kralj, Lado; Pekarna; slovenski literarni teoretiki; slovensko gledališče; teorija drame; zgodovinska avantgarda